The hydrography and dynamics of rings and eddies of the Agulhas retroflection February-March 1987 - Rigg, Gordon Maynard (Department of Oceanography, 2016)
The Agulhas Retroflection south of Africa is a dynamic region from which mesoscale rings and eddies are shed. Hydrographic data collected simultaneously during two dedicated research cruises in the Agulhas Retroflection region in February - March 1987 are analyzed in conjunction with satellite data (Thermal Infrared Imagery and Geosat Altimetry). An unusual and possibly atypical situation is documented where a total of six Agulhas rings and eddies were present in the Retroflection region. Each of the six vortices exhibited characteristics specific to their age and location within the Retroflection region. Bibliography: pages 195-210.